First-principles analysis of how Cobalt doping affects the structural, electronic, and optical properties of α-MoO3 - Rahman, Md. Ferdous; Melody, Zinat Rahman; Ali, Md. Hasan; Ghosh, Avijit; Barman, Pobitra; Islam, Md. Rasidul; Hossain, M. Khalid (Indian journal of physics, 2024)
Inbuilt high energy band gap and resistivity cause harm to the intrinsic molybdenum trioxide (MoO 3 ) for utilizing it directly in gas sensing and optoelectronic devices. Doping with transition metal ions can be an optimistic solution to these problems. By doping four side of modification of a material is possible. At first, doping can curtail the width of the energy band of semiconductor materials, thereby largely boosting the photo-sensitivity of the material and intensifying the light consumption that is more suitable for anti-laser devices and light source substances. The second is that doping can widen the material's band gap, which can significantly reduce the purities of the substance, improve absorbance, and make it suitable for strong interference semiconductor films and aperture materials. Third, changing the material's charge carrier density and effective mass can significantly improve conductivity. This is mostly relevant for conductive devices and photosensitive materials. Finally, changing the material's valance electron location influences the magnetic moment created by the spin of elementary particles in the entire system, allowing the magnetic characteristics of the substance to be regulated, which is especially useful for diluted magnetic semiconductor (DMS) materials. The investigation report of the structural, electrical, and optical characteristics of Cobalt (Co)-doped orthorhombic-phase MoO 3 utilizing plane-wave pseudo-potential technique based on first-principles computation is presented in this paper. The computation has been executed using density a functional theory (DFT)-based CASTEP computer program with the generalized gradient approximation (GGA) together with the Perdue-Burke-Ernzerhof (PBE) exchange–correlation function. Acquired structural parameters present good consistency with the former reported experimental data. The resultant electronic band structure reveals that pure MoO 3 shows an indirect energy band gap of 1.873 eV/2.312 eV whereas Co doping causes band narrowing of about 0.94 eV/1.36 eV with PBE/HSE techniques. The total and partial density of states (PDOS) have been studied comparatively, for pure and Co-doped MoO 3 , respectively. The absorption coefficient, loss function, reflectivity, refractive index, extinction coefficient, dielectric function, along with optical conductivity have also been determined to analyze the optical properties of Co-doped MoO 3 . Co-doped MoO 3 offers higher conductivity while decreasing resistivity, compared to the undoped case. The present study ensures that Co-doped α- MoO 3 can be competently employed as a functional material in gas sensing and optoelectronic devices.